2022
DOI: 10.1039/d2qo01322c
|View full text |Cite
|
Sign up to set email alerts
|

Rh(iii)-catalyzed substrate-dependent oxidative (spiro)annulation of isoquinolones with diazonaphthoquinones: selective access to new spirocyclic and oxepine-fused polycyclic compounds

Abstract: Reported herein is a practical and selective assembly of novel isoquinolone-containing spirocyclic and oxepine-fused polycyclic skeletons through a rhodium(III)-catalyzed oxidative [4+1] spiroannulation or formal [4+3] annulation reactions of diverse NH-isoquinolones...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Representative reported examples of oxidative annulation of isoquinolones, with alkenes by Li, [6a] Liu, [6b] and Kumar [6c] groups, with diazo‐1,3‐indandiones by Fan et al, [7] with benzoquinone by Sahoo [8a] and wang group [8b] and oxidative spiro cyclization of 2‐arylquinazolinones with N‐substituted maleimides by Lee group [9] using metal catalysts are depicted in Scheme 1. Also There were reports of Rh(III) catalyzed oxidative annulation of isoquinolones with alkynes reported by Wang group, [10] and oxidative spirocyclization of isoquinolones with diazonaphthoquinonones by Fan group [11] . Further recent literature study suggested some reports of Rh(III) catalyzed spiroannulation and fusion of maleimides with N‐(Phenylsulfonyl)acetamides by Fan group, [12] and with 2‐arylbenzimidazoles by Lee group [13] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Representative reported examples of oxidative annulation of isoquinolones, with alkenes by Li, [6a] Liu, [6b] and Kumar [6c] groups, with diazo‐1,3‐indandiones by Fan et al, [7] with benzoquinone by Sahoo [8a] and wang group [8b] and oxidative spiro cyclization of 2‐arylquinazolinones with N‐substituted maleimides by Lee group [9] using metal catalysts are depicted in Scheme 1. Also There were reports of Rh(III) catalyzed oxidative annulation of isoquinolones with alkynes reported by Wang group, [10] and oxidative spirocyclization of isoquinolones with diazonaphthoquinonones by Fan group [11] . Further recent literature study suggested some reports of Rh(III) catalyzed spiroannulation and fusion of maleimides with N‐(Phenylsulfonyl)acetamides by Fan group, [12] and with 2‐arylbenzimidazoles by Lee group [13] .…”
Section: Introductionmentioning
confidence: 98%
“…Also There were reports of Rh(III) catalyzed oxidative annulation of isoquinolones with alkynes reported by Wang group, [10] and oxidative spirocyclization of isoquinolones with diazonaphthoquinonones by Fan group. [11] Further recent literature study suggested some reports of Rh(III) catalyzed spiroannulation and fusion of maleimides with N-(Phenylsulfonyl)acetamides by Fan group, [12] and with 2-arylbenzimidazoles by Lee group. [13] Herein, we report a Ru(II)-catalyzed oxida-tive, dehydrogenative CÀ C followed by CÀ N coupling to produce fused and spirocylized products through CÀ H activation mechanism (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou demonstrated a strategy for the synthesis of spirocyclic indazole derivatives via Rh­(III)-catalyzed C–H activation and spiroannulation . Guo et al reported a [4 + 1] spiroannulation between isoquinolones and diazo compounds to access spirocyclic indazole compounds . Yang successfully coupled 2-(2-bromophenyl)-1 H -benzo­[ d ]­imidazoles with 1,2-diketones by a copper catalyst through arylation/cyclocondensation .…”
Section: Introductionmentioning
confidence: 99%
“… 5 Guo et al reported a [4 + 1] spiroannulation between isoquinolones and diazo compounds to access spirocyclic indazole compounds. 6 Yang successfully coupled 2-(2-bromophenyl)-1 H -benzo[ d ]imidazoles with 1,2-diketones by a copper catalyst through arylation/cyclocondensation. 7 Dong disclosed a copper-catalyzed organic ligand-promoted coupling reaction between 2-(2-bromophenyl)-1 H -benzo[ d ]imidazoles and cyclohexane-1,3-diones via an α-arylation/intramolecular nucleophilic addition cascade for the synthesis of benzimidazole-fused quinolines ( Scheme ) 1 8a .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of polyheterocyclic structures based on privileged scaffolds containing 6/7/5-fused heterocyclic components is of tremendous importance in modern organic chemistry. 1 Among them, oxazepine, oxazine, thiazine, and imidazole ring systems are privileged structural motifs in a wide variety of natural products and biologically active molecules. 2 Some drug structures such as rocastine (antihistamine), 3 piclozotan (treatment of Parkinson), 4 levofloxacin (antibiotic), 5 chlorpromazine (treatment of psychosis), 6 and omeprazole (proton pump inhibitor) 7 are illustrated in Fig.…”
mentioning
confidence: 99%